FREE NUTRITIOUS SCHOOL MEAL PROGRAMS IN INDONESIA AND THE NETHERLANDS: A COMPARATIVE ANALYSIS OF LEGAL FOUNDATIONS AND CONSTITUTIONAL RIGHTS: PROGRAM MAKANAN BERGIZI GRATIS DI SEKOLAH INDONESIA DAN BELANDA: ANALISIS PERBANDINGAN LANDASAN HUKUM DAN HAK KONSTITUSIONAL - Mulyosudarmo, Suviana Suwoto; Cornelis, Vieta Imelda; Siregar, Fritz Edward; P, Siti Marwiyah; Prawesthi, Wahyu (Pusat Studi Konstitusi dan Perundang-undangan, 2025)
This research aims to analyze the weaknesses, strengths, opportunities and risks of the Free Nutritious Food policy implementation in Indonesia and the Netherlands. In addition, the researcher also compares the findings with the experiences of a number of developed countries that have previously implemented similar policies, in order to assess the extent to which this policy can be adapted in Indonesia. The approach used in this research is normative legal research, which examines legislation, policy documents, and relevant academic literature as the basis for preparing legal arguments related to the feasibility and impact of the program. The focus of the analysis lies on the compatibility of the free lunch policy with the national legal framework, including the identification of the need for regulatory reform if necessary. Through this comparative study, the research also highlights institutional readiness and public support as crucial factors in ensuring the sustainability of the program. The results are expected to provide policy recommendations that are not only socially and economically contextualized, but also aligned with Indonesia's legal system and support the national development agenda.